A Dual-Functional and Efficient MOF-5@MWCNTs Electrochemical Sensing Device for the Measurement of Trace-Level Acetaminophenol and Dopamine - Jianxia Gu; Shuting Lang; Zhanbin Jin; Tingting Wei (Molecules)
The design and construction of dual-functional and high-efficiency electrochemical sensors are necessary for quantitative detection. In this work, a zinc-based metal–organic framework (MOF-5) and multi-walled carbon nanotubes (MWCNTs) were combined in situ through a simple solvothermal reaction to obtain an MOF-5@MWCNTs composite. The composite exhibits a large surface area, hierarchical pore structure, excellent conductivity, and enhanced electrochemical performance in the detection of acetaminophenol (AP) and dopamine (DA). Remarkably, the synergistic effects between MOF-5 and MWCNTs enable the electrochemical sensor based on the MOF-5@MWCNTs composite to quantitatively determine AP and DA at trace levels. Under optimal conditions, the proposed sensor features relatively wide linear ranges of 0.005–600 μM and 0.1–60 μM for AP and DA, respectively, with very low detection limits (LODs) of 0.061 μM and 0.0075 μM for AP and DA. Importantly, this electrochemical sensor demonstrates excellent reproducibility, stability, and anti-interference ability, making it suitable for practical applications in the detection of AP and DA in urine and tap water samples with acceptable recoveries. The successful integration of MOF-5 with MWCNTs results in a robust and versatile electrochemical sensing platform for the rapid and reliable detection of AP and DA at trace levels.